The Effect Of Government Expenditure, Investments And Export On Ecocomic Growth In Aceh - Zakiah Zakiah; Suyanti Kasimin; Anwar Deli (Proceedings of AICS - Social Sciences, 2019)
The aims of this study is to analyze how the effect of government expenditure, investment and exports on economic growth in Aceh. It uses time series in 2003-2018. Data were analyzed  using OLS method. The results show that increasing government expenditure, investment and exports can increase economic growth, however only government expenditure and exports have a statistically significant effect on economic growth, while investment in the form of foreign investment and domestic investment has no significant effect. Therefore, it is hoped that the Aceh government will be able to carry out development programs by improving the export structure by increasing the added value of export commodities, improving infrastructure, especially in rural areas and being able to allocate funds effectively and efficiently.